Protective and curative effects of Boerhaavia diff usa L. against fl uoride induced renal oxidative stress and antioxidant enzymes in rats - Shashi A; Jawant Kaur (Archives of Anatomy and Physiology - Peertechz Publications, 2017)
This work elucidated the protective effect of leaf extract of the Boerhaavia diffusa L. (punarnava) on kidney damage following fl uoride administration in rats. Forty eight rats were randomly divided into eight group's six rats in each. Group I was administered deionized water orally served as control. Group II and III were administered with 300 and 600 ppm NaF/kg bw/day for 40 days. Group IV were orally administrated with 500mg/kg b.w/day of leaf extract of Boerhaavia diffusa L. for 20 days Group V and VI were pre treated with 500 mg/kg bw/day of leaf extract of the Boerhaavia diffusa L. for 20 days and then exposed to 300 and 600 ppm NaF/kg bw/day for 40 days. Group VII and VIII were exposed fi rstly to 300 and 600 ppm NaF/kg bw/day and then post-treated with leaf extract of the Boerhaavia diffusa L. for 20 days. The level of MDA exhibited signifi cantly (p<0.001) increase while GSH and activities of SOD, CAT, and GPx revealed signifi cant (p<0.001) decline in kidney of rats treated with 300 and 600 ppm of NaF. The results indicate that pre and post-treatment signifi cantly decrements (p<0.001) in the activity of antioxidant enzymes superoxide dismutase (SOD), catalase (CAT), reduced glutathione (GSH) and glutathione peroxidise (Gpx) alongwith signifi cant increase (p<0.001) in the level of malondialdehyde (MDA).The current work suggests that the leaf extract of Boerhaavia diffusa L conferred therapeutic benefi ts on NaF-induced nephrotoxicity, particularly when administered before more than after the insult.